EVALUASI KEBIJAKAN PEMERINTAH DESA DALAM PEMBERHENTIAN DAN PENGANGKATAN PERANGKAT DESADI DESA TABANG BARAT - sardinandus nandus; Muhammad Massyat; Nur Fitrah (Journal Peqguruang: Conference Series, 2025)
This research aims to provide an overview of how to evaluate village government policies in the dismissal and appointment of village officials in West Tabang Village, Tabang District, Mamasa Regency. This type of research uses a qualitative approach. Qualitative descriptive research is research that aims to describe and describe events and phenomena that occur in the field and present data systematically, factually and accurately regarding facts or phenomena that occur in the field. Data collection was carried out using observation, interviews and documentation techniques. The results of this research provide data that the evaluation of the Village Government's policy in dismissing and appointing village officials in West Tabang Village has been carried out in accordance with the applicable regulations contained in Permendagri number 67 of 2017. This is to ensure that the Village Government's regulations and exceptions are carried out in an appropriate manner. tested and predicted not based on different feelings of preference for particular individuals. Evaluation of the policy of the Tabang village government, Tabang sub-district, Mamasa district regarding the appointment and dismissal of village officials is in accordance with applicable regulations. Starting from effectiveness, efficiency, adequacy, alignment and responsiveness, it has been carried out in accordance with applicable regulations. The appointment and dismissal of village officials is carried out in a tested manner so that village officials can carry out their duties well in accordance with expectations. And the rumors circulating about unilateral dismissal are only rumors from the community and do not correspond to the facts of what happened.